2017
DOI: 10.4269/ajtmh.16-0373
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Sensitivity of Cutaneous Leishmania Promastigote Isolates Circulating in French Guiana to a Set of Drugs

Abstract: Abstract. Anti-leishmaniasis drug resistance is a common problem worldwide. The aim of this study was to inventory the general in vitro level of sensitivity of Leishmania isolates circulating in French Guiana and to highlight potential in vitro pentamidine-resistant isolates. This sensitivity study was conducted on 36 patient-promastigote isolates for seven drugs (amphotericin B, azithromycin, fluconazole, meglumine antimoniate, miltefosine, paromomycin, and pentamidine) using the Cell Counting Kit-8 viability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…(V . ) braziliensis present a range of susceptibility that is much wider than previous reports [ 24 , 46 , 47 ]. The reverse was found for L .…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…(V . ) braziliensis present a range of susceptibility that is much wider than previous reports [ 24 , 46 , 47 ]. The reverse was found for L .…”
Section: Discussionmentioning
confidence: 69%
“…(V . ) braziliensis isolates from French Guiana [ 24 ]. The authors reported EC 50 values with wide variability, ranging between 1.03 and >25 μg/ml AmB for L .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this determination could be biased by many confounding factors that can reduce lab-to-lab reproducibility and lead to false hit discoveries. These factors could include macrophage infection rate, incomplete amastigogenesis, impact of distinct culture media, as well as the intrinsic pathogenicity of the strain selected for the assay [ 39 , 40 , 41 ].…”
Section: Trypanosomatids′ Life Cycle In the Context Of In Vitro Scmentioning
confidence: 99%